A Model of Competency Development for Thai Language Teachers in International Schools - จุฑาพรมณี, ครรชิต (Academic Journal Phranakhon Rajabhat University, 2017)
The objectives of this research are: 1) to create a model of competency development for Thai language teachers in international schools; 2) to assess the feasibility of a model of competency development for Thai language teachers in international schools. The research was divided into four steps: Step 1. To study of the problems and needs of the internal supervision in the competency of Thai language teachers in international schools by synthesizing concepts and theories, the research from both domestic and international and to study the real competency of Thai language teachers in international schools. This was done by interviewing 15 international school administrators and experts to set a framework for the research. Step 2. To create a model of competency development for Thai language teachers in international schools. Step 3. To determine the suitability of a model of competency development for Thai language teachers in international schools by holding Focus Group discussions with the experts and validate the model. Step 4. To assess the feasibility of a model of competency development for Thai language teachers for international schools by questionnaire from 69 school administrators, Thai Heads of Department and Thai teachers who have been specifically selected. The instrument was valid to an average of 0.95 according to average (X) and the standard deviation (S.D.). The data was then revised to help develop the guidelines for internal supervision for the research in the classroom. The research found that A model of competency development for Thai Language teachers in international schools consisted of five components: 1) Principle and reasons 2) The purpose of the guidelines 3) The essence of a model of competency development for Thai language teachers in international school which consisted of four phases: 1) current education, problems and needs; 2) planning and choice determination; 3) operation on competency development; 4) evaluation on competency development. 4) Guidelines for the operation 5) Successful condition for operation. The operation of competency development for Thai language teachers in international schools in consists of seven competencies: 1) knowledge and professional skills 2) the ability to use English for communication 3) self-development 4) learning management and curriculum development 5) development of learners 6) class management 7) personal characteristics. This approach is appropriate with the highest level of overall average at ( X = 4.62). A model of competency development for Thai language teachers in international schools is possible to implement and operate in schools. The overall elements have an average level of (X = 4.29) when considering each component in descending order from the most to the least, they are: planning and choice determination; current education, problems and needs; evaluation on competency development and operation on competency development respectively. When considering the possibility of a model of competency development for Thai language teachers in international schools in descending order from the most to the least, they are: The ability to use English for communication (X = 4.42); Development of learners (X = 4.36); Class management (X = 4.35); Knowledge and professional skills (X = 4.32); Self- development (X = 4.26); Learning management and curriculum development (X = 4.24) and Personal characteristics (X = 4.23) respectively Keywords: Competency Development / Thai Language Teachers/ International School